Perceptions of the Benefits of ICT on Teacher Performance at Santa Lusia Sei Rotan Middle School - Sidabutar, Hotmaida; Purba, Saud; Rangkuti, Irsan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Santa Lusia Junior High School is a junior high school in Medan City, precisely in Sei Rotan, where this school is located in the Batang Kuis area, Desli Serdang District, North Sumatra. In the application of the learning process carried out by several existing teachers, there are still many teachers who apply learning models that do not apply digital-based information and communication technology (ICT), where the learning models and methods carried out still use learning methods that is no longer relevant to the development of learning, so that it will affect the ability of students to understand, describe, and master the material taught which in the end students follow the old system by remembering and memorizing, not understanding the learning material, because teachers at Santa Lucy Junior High School apply a memorization and remembering system instead of increasing literacy skills to master the existing material. In addition, some teachers at Santa Lucy Junior High School still do not understand the use and benefits of information and communication technology for the learning process and can be used as new learning models and methods, where the lack of understanding makes teachers at Santa Lucy Junior High School less understand and know that the benefits of information and communication technology are very important for improving the quality of learning, and improving the quality and capacity of teachers for the better. The research method used is a quantitative descriptive research method, where the results of the study explain that the benefits of ICT have a positive and significant effect on teacher performance at Santa Lusia Sei Ratan Junior High School, where by using ICT in the learning process is expected to improve teachers' ability to understand learning material used to increase students' understanding and ability to master learning material.